LncRNA LINC00969 promotes acquired gefitinib resistance by epigenetically suppressing of NLRP3 at transcriptional and posttranscriptional levels to inhibit pyroptosis in lung cancer - Jiali Dai; Tianyu Qu; Dandan Yin; Yanan Cui; Chen Zhang; Erbao Zhang; Renhua Guo (Cell Death and Disease, 2023)
Abstract Epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) treatment prolongs the survival of lung cancer patients harbouring activating EGFR mutations. However, resistance to EGFR-TKIs is inevitable after long-term treatment. Molecular mechanistic research is of great importance in combatting resistance. A comprehensive investigation of the molecular mechanisms underlying resistance has important implications for overcoming resistance. An accumulating body of evidence shows that lncRNAs can contribute to tumorigenesis and treatment resistance. By bioinformatics analysis, we found that LINC00969 expression was elevated in lung cancer cells with acquired gefitinib resistance. LINC00969 regulated resistance to gefitinib in vitro and in vivo. Mechanistically, gain of H3K4me1 and H3K27Ac led to the activation of LINC00969 expression. LINC00969 interacts with EZH2 and METTL3, transcriptionally regulates the level of H3K27me3 in the NLRP3 promoter region, and posttranscriptionally modifies the m6A level of NLRP3 in an m6A-YTHDF2-dependent manner, thus epigenetically repressing NLRP3 expression to suppress the activation of the NLRP3/caspase-1/GSDMD-related classical pyroptosis signalling pathways, thereby endowing an antipyroptotic phenotype and promoting TKI resistance in lung cancer. Our findings provide a new mechanism for lncRNA-mediated TKI resistance from the new perspective of pyroptosis via simultaneous regulation of histone methylation and RNA methylation. The pivotal role of LINC00969 gives it the potential to be a novel biomarker and therapeutic target for overcoming EGFR-TKI resistance in lung cancer.